21.0%‐efficient co‐diffused screen printed n‐type silicon solar cell with rear‐side boron emitter. Issue 2 (2nd December 2015) - Wehmeier, Nadine; Lim, Bianca; Nowack, Anja; Schmidt, Jan; Dullweber, Thorsten; Brendel, Rolf
Abstract : Plasma enhanced chemical vapor deposition (PECVD) is applied to deposit boron silicate glasses (BSG) acting as boron diffusion source during the fabrication of n‐type silicon solar cells. We characterize the resulting boron‐diffused emitter after boron drive‐in from PECVD BSG by measuring the sheet resistances R sheet, B and saturation current densities J 0, B . For process optimization, we vary the PECVD deposition parameters such as the gas flows of the precursor gases silane and diborane and the PECVD BSG layer thickness. We find an optimum gas flow ratio of SiH4 /B2 H6 = 8% and layer thickness of 40 nm. After boron drive in from these PECVD BSG diffusion sources, a low J 0, B values of 21 fA/cm 2 is reached for R sheet, B = 70 Ω/□. The optimized PECVD BSG layers together with a co‐diffusion process are implemented into the fabrication process of passivated emitter and rear totally diffused (PERT) back junction (BJ) cells on n‐type silicon. An independently confirmed energy conversion efficiency of 21.0% is achieved on 15.6 × 15.6 cm 2 cell area with a simplified process flow. This is the highest efficiency reported for a co‐diffused n‐type PERT BJ cell using PECVD BSG as diffusion source. A loss analysis shows a small contribution of 0.13 mW/cm 2 of the boron diffusion to the recombination loss proving the high quality of this diffusion source. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : The fabrication of silicon solar cells is simplified by applying an alternative diffusion source and a co‐diffusion process. A boron silicate glass (BSG) is plasma‐deposited and capped with a silicon nitride (SiN z ). During a co‐diffusion, boron is diffused from the BSG and phosphorus is diffused from the POCl3 gas into the n‐type substrate. The screen‐printed solar cells reach 21.0% efficiency.